NASM essentials of personal fitness training - McGill, Erin A.; Montel, Ian N. (Jones and Bartlett Learning, 2017)
"This edition employs features that make content more digestible and turn theory into practice. Chapters thread science throughout the text to enhance learning and contextual understanding. Based on NASM's proprietary OPTTM model, you will learn a systematic approach to program design with exercise program guidelines and variables; protocols for building stabilization, strength, and power programs; and more"--